EFFECTIVENESS OF CAST POLYMER-SULFUR ASPHALT CONCRETE TECHNOLOGY FOR OPERATIONAL CONDITIONS WITH HIGH TEMPERATURES - Sadikov Ibragim Salikhovich; Tilakov Sukhrob Mukhammadiyevich (European Science Publishing, 2024)
The article analyzes existing technologies of cast asphalt concrete and cast sulfur asphalt concrete. A new composition of the cast polymer-sulfur asphalt concrete mixture has been developed, and the improved performance indicators of the cast polymer-sulfur asphalt concrete coating, manufactured according to the new composition, in particular, crack resistance and high-temperature resistance, have been experimentally scientifically substantiated.
Keywords: cast polymer asphalt concrete, cast asphalt concrete, optimal composition, granulometric composition, sand, gravel, mineral powder, bitumen, temperature, sulfur, modified sulfur, sulfur bitumen, asphalt concrete compressive strength limit, asphalt concrete water saturation, asphalt concrete water resistance.